Vector Analysis of Astigmatism in Keratoconic Eyes After Combined Intrastromal Corneal Ring Segments Implantation and Collagen Cross-Linking - Abozaid MA (Dove Medical Press, 2020)
Mortada Ahmed Abozaid,1 Abdelsalam Abdalla2 1Faculty of Medicine, Sohag University, Sohag, Egypt; 2Faculty of Medicine, Assiut University, Assiut, EgyptCorrespondence: Mortada Ahmed AbozaidOphthalmology Department, Faculty of Medicine, Sohag University, Sohag, EgyptTel +20 932 309 244Fax +20 932 325 531Email mourtada_abdelaal@med.sohag.edu.egPurpose: To analyze astigmatic changes after intrastromal corneal ring segments (ICRSs) implantation accompanied by corneal collagen cross-linking (CXL) in keratoconic eyes using the Alpins vectorial method.Patients and Methods: Twenty-eight eyes of 18 patients with keratoconus were included in this retrospective non-comparative study. All patients had combined femtosecond laser-assisted Keraring implantation and CXL, and completed at least 2 years of follow-up. Both manifest and corneal astigmatic changes were analyzed using the Alpins vectorial parameters based on 3 vectors; target induced astigmatism (TIA), surgically induced astigmatism (SIA) and difference vector (DV).Results: Regarding analysis of manifest astigmatism, the TIA arithmetic mean was 5.22 D while the vector mean was 3.13 D Ax 173. The SIA arithmetic mean was 5.41 D while the vector mean was 2.38 D Ax 173. The DV arithmetic mean was 2.10 D while the vector mean was 0.75 D Ax 175. Regarding analysis of corneal astigmatism, the TIA arithmetic mean was 5.22 D while the vector mean was 3.13 D Ax 173. The SIA arithmetic mean was 5.23 D while the vector mean was 1.8 D Ax 12. The DV arithmetic mean was 4.28 D while the vector mean was 2.04 D Ax 157.Conclusion: Vector analysis of manifest and corneal astigmatism in keratoconic eyes with previous ICRS and CXL reveals more accuracy and predictability of manifest refraction in calculating SIA.Keywords: Alpins method, astigmatic correction in keratoconus, kerarings, vector analysis